Regional differences in educational achievement: A replication study of municipality data - Boman, Björn (Frontiers in Education, 2022)
The current study analysed the relationships between explanatory variables such as socioeconomic status (SES), migration background (MB), and formal teacher competence, and aggregated grades in the Swedish lower-secondary school context by using aggregated municipality data from 2013 and 2018. The aim was to replicate the findings from a similar study, as well as to expand the previous study by including more control variables, a combination of data sets from different years, and various robustness checks. Overall, the findings were similar in regard to effect sizes and the magnitude and order of these relationships. However, the SES indicators had larger effect sizes when data from different years were merged and when the outcome variable was changed to an alternative measure of educational achievement. In one model, the MB variable even became statistically insignificant. These results indicate that SES is an important variable which explains a substantial amount of variance in regard to school achievement indicators such as grade point average. Nonetheless, aggregated data may still suffer from omitted variable bias and biased effect size estimates.